Antideuteron production in γ(nS) decays and in e+e- → qq [bar] at √s [approximately] 10.58GeV - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
We present measurements of the inclusive production of antideuterons in e+e− annihilation into hadrons at ≈10.58 GeV center-of-mass energy and in Υ(1S,2S,3S) decays. The results are obtained using data collected by the BABAR detector at the PEP-II electron-positron collider. Assuming a fireball spectral shape for the emitted antideuteron momentum, we find B(Υ(1S)→¯dX)=(2.81±0.49(stat)+0.20−0.24(syst))×10−5, B(Υ(2S)→¯dX)=(2.64±0.11(stat)+0.26−0.21(syst))×10−5, B(Υ(3S)→¯dX)=(2.33±0.15(stat)+0.31−0.28(syst))×10−5, and σ(e+e−→¯dX)=(9.63±0.41(stat)+1.17−1.01(syst) fb.